Immune Checkpoint Inhibitors and Immune-Related Adverse Drug Reactions: Data From Italian Pharmacovigilance Database - Ruggiero, Rosanna; Fraenza, Federica; Scavone, Cristina; di Mauro, Gabriella; Piscitelli, Raffaele; Mascolo, Annamaria; Ferrajolo, Carmen; Rafaniello, Concetta; Sportiello, Liberata; Rossi, Francesco; Capuano, Annalisa (Frontiers in Pharmacology, 2020)
Background The introduction of immune checkpoint inhibitors (ICIs) in clinical practice has brought significant benefits for patients. Seven ICIs are available in Europe: nivolumab, pembrolizumab, atezolizumab, avelumab, durvalumab, cemiplimab and ipilimumab. Despite their proven clinical efficacy, these innovative drugs may cause serious immune-related adverse drugs reactions (irADRs). Given the significance of these ADRs for patients’ health, we analyzed individual case safety reports (ICSRs) related to ICIs, focusing on those reporting irADRs, collected in the Italian spontaneous reporting database. Methods We analyzed ICI-induced irADRs collected in the Italian Pharmacovigilance database (Rete Nazionale di Farmacovigilanza – RNF) from January 1st 2002 to February 28th 2019, focusing on those reported in the Campania Region. We retrieved from an open-access Italian pharmacovigilance system, the RAM system (for national safety data), and from the RNF (for Campania safety data) all ICSRs reporting ADRs related to ICIs authorized until the analysis date. Focusing on irADRs, we performed descriptive and disproportionality analyses through the reporting odds ratio (ROR) with 95% confidence interval. Results National results. Among 2,088 ICIs-related ICSRs, 801 reported irADRs. The majority of such ADRs occurred in male patients reporting gastrointestinal and skin toxicities. Nivolumab and pembrolizumab were drugs most commonly reported as suspect drugs. Compared to other ICIs, ROR was statistically significant for pembrolizumab and ipilimumab. Campania Region results. Out of 253 ICIs-related ICSRs sent to Regional Pharmacovigilance Center of Campania Region, 121 reported at least one ICIs-induced irADR. These were serious in 37.2% of cases and had an unfavorable outcome in 32.2% of cases. Overall, out of 8 ICSRs reported ADR with a fatal outcome, 4 reported irADRs. From disproportionality analyses on regional ICSRs, statistically significant ROR emerged only for ipilimumab. Conclusions Our results showed that during the study period several serious irADRs were reported, some of which had fatal outcome. Given the clinical relevance of irADRs, further investigations in real-life context are necessary for a better characterization of ICIs safety profiles. Oncologists should be trained to early recognize and adequately manage irADRs. Patients should also be educated to immediately report any new symptom or worsening of pre-existed ones during the ICI treatment.